Study of the drying kinetics and calculation of mass transfer properties in hot air drying of Cynara cardunculus - Guiné, Raquel (2020)
In the present work, mass transfer properties of thistle flower (Cynara cardunculus L.) were evaluated for the convective drying carried out at temperatures between 35 and 65°C, with an air flow of 0.5 m/s. The calculations followed two different algorithms, based on mathematical models derived from the thin layer drying equation and Fick’s second law of diffusion. The results obtained indicated that different methodologies resulted in different values of mass transfer properties, which is an alert that care must be taken when choosing which calculation method might be more appropriate in a specific practical application. In all cases, the values of moisture diffusion and mass transfer coefficient were found to increase with increasing operating temperature. The values of diffusivity increased from 2.7866 × 10−9 to 1.4027 × 10−8 m2/s for the thin layer model-based algorithm and from 1.9256 × 10−10 to 1.2033 × 10−9 m2/s for Fick’s equation model. The values of the mass transfer coefficient increased from 8.4335 × 10−8 to 8.4400 × 10−7 m/s and from 5.8277 × 10−9 to 7.2398 × 10−8 m/s, respectively, for the thin layer and Fick’s law-based models.